(untitled) (Fiep Bulletin - online, 2012)
The objective was to analyze the discourse of undergraduate students of physical education about the construction of masculinities in soccer. The issue of the research tries to answer this question: How are the physical education students’ discourses presented to what concerns to the construction of masculinities in soccer? The type of research was of descriptive method of ethnographic character qualitative nature. All the samples were randomly chosen and the participants are all EEFD/UFRJ students (Physical education college/ Federal university of Rio de Janeiro), of both genders and different terms. The instrument was a semi-structured interview and as an analysis technique we use the discourse. The results found were grouped as: 1- The so-called masculine activities versus the so-called feminine ones: a discourse about masculinity; 2- Soccer and the masculinities universe; 3- social differences versus gender differences. We can see that masculinities are not shown uniformly, highlighting the existence of hegemonic patterns and others subordinated to these. Our conclusion points to a reproduction of stereotypes, prejudice, resistance and new values and attitudes that magnify dominant views among men and women I the current society in gender relationships.